Representing Agrippina : constructions of female power in the early Roman Empire - Ginsburg, Judith (Oxford ; New York : Oxford University Press, 2006)
Provides a fresh look at both the literary and material representations of Agrippina. This study exposes both the contrivances of the commissioned artists whose idealized portraits served to buttress the image of the regime and the contrasting designs of the historians whose rhetorical stereotypes and negative depictions aimed to undermine it.
Introduction; Chapter 1: Agrippina in the Literary Tradition; Chapter 2: Visualizing Agrippina; Chapter 3: Agrippina and the Power of Rhetorical Stereotypes; Chart of the Julio-Claudians; Bibliography; Index
Includes bibliographical references (pages 135-141) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Agrippina, -- Minor, -- 15-59.; Agrippina, -- Minor, -- 15-59 -- In literature; Agrippina, -- Minor, -- 15-59 -- Portraits; Agrippina, -- Minor, -- 15-59; Rome -- History -- Julio-Claudians, 30 B.C.-68 A.D.; Empresses -- Rome -- Biography; Rome -- Histoire -- 30 av. J.-C.-68 (Julio-Claudiens); Impératrices -- Rome -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Ancient; Empresses; Literature; Rome (Empire); 30 B.C.-68 A.D; History; Biographies; Portraits; Biographies; Biographies